A method for increasing the efficiency of a wind turbine - Yershina, A.K.; Sakipova, S.E. (Eurasian Physical Technical Journal, 2020)
The article discusses the possibilities of improving the energy efficiency of wind turbines. A brief analysis of the current state of development of alternative energy, in particular wind energy in Kazakhstan, is considered. The computational study has shown that an increase in the power of a wind - power plant is possible due to the use of a system of simultaneously rotating rotors. A brief description of Bidarrieus-2 wind turbine construction, which can significantly increase the power removed from the wind flow, is given. The possibility of further increasing the efficiency of the Bidarrieus-2 wind turbine by means of a concentrator is discussed. The unique method for the speed controlling of the wind flow with the help of sliding flaps of the guide concentrator in order to improve the performance of the wind turbine at high wind speed is proposed first time.
Keywords: wind power; vertical-axial wind turbine; multy-rotor unit; Bidarrieus-2; wind energy utilization factor